Marketing strategy - Fifield Paul (Butterworth-Heinemann, 1992)
Strips away the confusion that surrounds marketing strategy. Marketing and strategy are about relationships between people and this is brought into focus in the text. Marketing practitioners should find this a handy book on the role of the marketing director in the organization of the 1990s.